2016
DOI: 10.1097/tp.0000000000000871
|View full text |Cite
|
Sign up to set email alerts
|

Eomesoderminlo CTLA4hi Alloreactive CD8+ Memory T Cells Are Associated With Prolonged Renal Transplant Survival Induced by Regulatory Dendritic Cell Infusion in CTLA4 Immunoglobulin–Treated Nonhuman Primates

Abstract: Background Memory T cells (Tmem), particularly those resistant to costimulation blockade (CB), are a major barrier to transplant tolerance. The transcription factor Eomesodermin (Eomes) is critical for Tmem development and maintenance, but its expression by alloactivated T cells has not been examined in non-human primates. Methods We evaluated Eomes and co-inhibitory cytotoxic T lymphocyte antigen-4 (CTLA4) expression by alloactivated rhesus monkey T cells in the presence of CTLA4 immunoglobulin (Ig), both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 65 publications
0
41
0
Order By: Relevance
“…α1-Antitrypsin-pulsed DC are characterized by decreased expression of MHC-II, CD80, and CD86 and high expression of IDO. After transferring these IDO + Tol-DC, the kidney allograft survival period is prolonged and Treg increase ( 87 ). Human soluble CD83 (hsCD83) is able to inhibit DC maturation and cause the anergy of Teff.…”
Section: The Function Of Tol-dcmentioning
confidence: 99%
See 1 more Smart Citation
“…α1-Antitrypsin-pulsed DC are characterized by decreased expression of MHC-II, CD80, and CD86 and high expression of IDO. After transferring these IDO + Tol-DC, the kidney allograft survival period is prolonged and Treg increase ( 87 ). Human soluble CD83 (hsCD83) is able to inhibit DC maturation and cause the anergy of Teff.…”
Section: The Function Of Tol-dcmentioning
confidence: 99%
“…Eomesodermin (Eomes), a key transcription factor in CD8 + Tmem ( 149 ), play a critical role in long-term survival of antigen-specific central Tmem. The prolonged survival of renal allografts after both CTAL4Ig and donor-derived Tol-DC therapy might be related to the maintenance of donor-reactive Eomes low CTLA4 high central Tmem, which displayed a regulatory phenotype in vivo ( 87 ). Compared to CNI, CTLA4Ig may preserve renal function and improve long-term outcomes in kidney transplantation ( 150 ).…”
Section: Preclinical and Clinical Attempts Of Tol-dc In Organ Transplmentioning
confidence: 99%
“…We have also reported that prolonged renal allograft survival in monkeys given donor‐derived DCreg is associated with an increased incidence of donor‐reactive CTLA4 hi CD8 + T cells expressing low levels of the memory cell survival factor Eomesodermin (Eomes) posttransplant. In monkeys given either no or unpulsed autologous DCreg, the incidence of donor‐reactive Eomes lo CTLA4 hi CD8 + T cells was reduced significantly 4 weeks posttransplant (median = 8.1%) compared to pretransplant (median = 16.6%) (p < 0.05), whereas in monkeys given Ag‐pulsed autologous DCreg, the incidence of this subset was increased posttransplant (median = 8.1%) compared to pretransplant (median = 5.5%) (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…During an innate immune response, DCs can sense pathogen derived molecular patterns (PAMPs) via pattern-recognition receptors (PRRs), and activate downstream inflammatory immune responses. [73][74][75][76][77][78][79][80][81] First of all, downregulation of MHC-II and costimulatory molecules impair their antigen presenting ability, promoting hypo-responsiveness of cognate alloreactive T cells. However, the presence of an innate immune response may alter the phenotype and function of DCs by promoting their activation F I G U R E 2 Effects of infection on the regulatory immune cell network.…”
Section: Regulatory Dendritic Cellsmentioning
confidence: 99%
“…72 Their tolerogenic efficacy in transplantation and mechanisms of action has been well-described in rodent and non-human primate (NHP) transplant models. [73][74][75][76][77][78][79][80][81] First of all, downregulation of MHC-II and costimulatory molecules impair their antigen presenting ability, promoting hypo-responsiveness of cognate alloreactive T cells. Second, Tol-DCs can induce apoptosis of both naive and memory T cells through activation of Fas/FasL pathway and upregulation of IDO.…”
Section: Cd4 + Cd25 + Foxp3 + Regulatory T Cellsmentioning
confidence: 99%